Pauline economy in the middle ages : "the spiritual cannot be maintained without the temporal ..." - Romhányi, Beatrix, 1967- (East Central and Eastern Europe in the Middle Ages, 450-1450, 2020)
In Pauline Economy in the Middle Ages ''The Spiritual Cannot Be Maintained Without The Temporal ...'' Beatrix F. Romhányi examines the estate management of the Pauline order - the only religious community native to medieval Hungary. Sources on the history, and especially on the economy, of the order have survived in exceptionally high numbers compared to other religious communities in Hungary. In the late Middle Ages, the order developed a unique estate management system. Based on the income of their landed estates and their privileges, the Paulines increasingly moved towards the capitalistic estate management around 1500, while donations, alms and annuities still composed a significant part of the incomes connecting the Paulines to the mendicant orders.